Effective deactivation of A549 tumor cells in vitro and in vivo by RGD-decorated chitosan-functionalized single-walled carbon nanotube loading docetaxel - Li, Bin; Zhang, Xiao Xue; Huang, Hao Yan; Chen, Li Qing; Cui, Jing Hao; Liu, Yanli; Jin, Hehua; Lee, Beom Jin; Cao, Qing Ri (International Journal of Pharmaceutics, 2018)
This study aims to construct and evaluate RGD-decorated chitosan (CS)-functionalized pH-responsive single-walled carbon nanotube (SWCNT) carriers using docetaxel (DTX) as a model anticancer drug. DTX was loaded onto SWCNT via π–π stacking interaction (SWCNT-DTX), followed by the non-covalent conjugation of RGD-decorated CS to SWCNT-DTX to prepare RGD-CS-SWCNT-DTX. The RGD-CS-SWCNT-DTX showed significantly higher drug release than the pure drug, giving higher release rate at pH 5.0 (68%) than pH 7.4 (49%). The RGD-CS-SWCNT-DTX could significantly inhibit the growth of A549 tumor cells in vitro, and the uptake amount of A549 cells was obviously higher than that of MCF-7 cells. Meanwhile, the cellular uptake of RGD-CS-SWCNT-DTX was higher than that of CS-SWCNT-DTX in A549 cells, mainly through clathrin and caveolae-mediated endocytosis. The RGD-CS-SWCNT-DTX significantly inhibited tumor growth of A549 cell-bearing nude mice through active tumor-targeting ability. Furthermore, no pathological changes were found in tissues and organs. The result demonstrated that RGD-CS-SWCNT-DTX displayed high drug loading, pH-responsive drug release, remarkable antitumor effect in vitro and in vivo, and also good safety to animal body.
Keywords: A549 Cells; Animals; Antineoplastic Agents; Cell Survival; Chitosan; Drug Carriers; Drug Liberation; Female; Humans; MCF-7 Cells; Mice, Inbred BALB C; Mice, Nude; Nanotubes, Carbon; Neoplasms; Oligopeptides; Taxoids; Tumor Burden; Xenograft Model Antitumor Assays; A549 cells; Chitosan; Docetaxel; RGD peptide; Single-walled carbon nanotube